2017
DOI: 10.1089/aid.2016.0153
|View full text |Cite
|
Sign up to set email alerts
|

High-Sequence Diversity and Rapid Virus Turnover Contribute to Higher Rates of Coreceptor Switching in Treatment-Experienced Subjects with HIV-1 Viremia

Abstract: Coreceptor switching from CCR5 to CXCR4 is common during chronic HIV-1 infection, but is even more common in individuals who have failed antiretroviral therapy (ART). Prior studies have suggested rapid mutation and/or recombination of HIV-1 envelope (env) genes during coreceptor switching. We compared the functional and genotypic changes in env of viruses from viremic subjects who had failed ART just before and after coreceptor switching and compared those to viruses from matched subjects without coreceptor sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 90 publications
(107 reference statements)
0
2
0
Order By: Relevance
“…We hypothesize that reshaping of naive and central memory CD4+ T cells harboring X4 species could be involved; CXCR4-using HIV strains predominate in these cells and there is a negative correlation between HCV RNA level and CD4 central memory frequency in HIV-HCV patients, who had a lower number of naive CD4+ cells with respect to HIV mono-infected subjects 26 28 . However, we cannot exclude the involvement of mechanism other than HCV cure, as heterozygosis for the CCR5D32 29 , 30 .…”
Section: Discussionmentioning
confidence: 96%
“…We hypothesize that reshaping of naive and central memory CD4+ T cells harboring X4 species could be involved; CXCR4-using HIV strains predominate in these cells and there is a negative correlation between HCV RNA level and CD4 central memory frequency in HIV-HCV patients, who had a lower number of naive CD4+ cells with respect to HIV mono-infected subjects 26 28 . However, we cannot exclude the involvement of mechanism other than HCV cure, as heterozygosis for the CCR5D32 29 , 30 .…”
Section: Discussionmentioning
confidence: 96%
“…X4 viruses have been shown to evolve from pre-existing R5 viral populations, with coreceptor switching being associated with high replication rates, but not selective pressure [ 3 ]. This coreceptor switching is more frequent in patients who have failed antiretroviral therapy (ART) [ 4 ], with immune activation correlating with X4 tropism [ 5 ]. A simulation study of a stochastic model showed that coreceptor switching occurs from 6 to more than 27 years after infection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%